2010
DOI: 10.2903/sp.efsa.2010.en-53
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term dietary exposure to different food colours in young children living in different European countries

Abstract: In this document, we report on the long-term dietary exposure to 40 different food colours in young children living in 11 European countries. Food consumption data of children aged 1 up to 10 years (in Cyprus 11 up to 14 years) were combined with food colour concentrations as supplied by EFSA using statistical models to calculate exposure. Food consumption data were all categorised according to a harmonised system to allow for linkage with food colour concentration data in a standardised way. Two different exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 5 publications
0
26
0
3
Order By: Relevance
“…On the contrary, for older people, one could imagine a more limited intake via coffee creamer in certain other countries compared to the Netherlands, however, in other countries other particular products could be main contributors. The variability in E 171 intake does not have to be that great, as, for example, the estimated intake of E 171 by children determined in different European countries according to the Expochi study was demonstrated to only vary about three-fold (Huybrechts et al, 2010), although the intake estimation in that study was conducted less sophisticatedly as has been performed in the present study. Still, it would be very interesting to determine TiO 2 intake levels for other populations as well, especially with regard to the limited margin of exposure as calculated for TiO 2 NPs (Heringa et al, submitted).…”
Section: Comparison Of Measured Ti Levels To Ti Levels Reported In LImentioning
confidence: 59%
See 2 more Smart Citations
“…On the contrary, for older people, one could imagine a more limited intake via coffee creamer in certain other countries compared to the Netherlands, however, in other countries other particular products could be main contributors. The variability in E 171 intake does not have to be that great, as, for example, the estimated intake of E 171 by children determined in different European countries according to the Expochi study was demonstrated to only vary about three-fold (Huybrechts et al, 2010), although the intake estimation in that study was conducted less sophisticatedly as has been performed in the present study. Still, it would be very interesting to determine TiO 2 intake levels for other populations as well, especially with regard to the limited margin of exposure as calculated for TiO 2 NPs (Heringa et al, submitted).…”
Section: Comparison Of Measured Ti Levels To Ti Levels Reported In LImentioning
confidence: 59%
“…The dietary intake of TiO 2 has been calculated in previous years by Penttilä et al (1988), by the consortium of the Expochi project for EFSA (Huybrechts et al, 2010), and by Weir et al (2012). The dietary intake varied 1300-fold between 0.01 and 13.0 mg TiO 2 /kg bw/d.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food additives are chemicals in the food supply which are closely regulated to ensure they do not provide any risk to human health (72) ; exposure assessments are fundamental to ensuring that there is no concern from the intakes of such chemicals in the diet, and can provide valuable information for risk assessors (59) and manufacturers (56) . There is a high level of interest in the area of additives and young children, which is focused primarily on the behavioural effects of these food chemicals (62)(63)(64)(65)(66)(67)(68)(69) ; however, it is important to consider the limitations of the available scientific studies when interpreting results.…”
Section: Discussionmentioning
confidence: 99%
“…To date, four different risk assessments have been carried out (Pb, Cr, Se and food colours). Their report on food colours (59) utilised food consumption data from eleven countries to examine long-term exposure to forty different food colourings. This report illustrated that different countries had different levels of exposure and emphasised the need for a harmonised approach in food consumption data collection within Europe.…”
Section: Exposure Assessments In Preschool Childrenmentioning
confidence: 99%